SAT0109 Expression of bcl-2 in juvenile chronic arthritis. (1st June 2001) - Tuszkiewicz-Misztal, E; Bojarska-Junak, A; Krawczyk, P; Roliñski, J; Opoka-Winiarska, V
Abstract : Background: The aim of this study was to investigate the relationship between levels of molecules regulating of apoptosis in T lymphocytes and the clinical manifestation of juvenile chronic arthritis (JCA). Objectives: Apoptosis is involved in the regulation of an immune response to foreign and autoantigens. We determined the expression of Bcl-2 mitochondrial oncoprotein, which inhibit apoptosis, in different subtypes of lymphocytes obtained from peripheral blood from healthy children (n = 14, age:12, 4 ± 5, 4) and JCA patients with pauciarticular onset (n = 17, age: 12, 2 ± 3, 8) and polyarticular onset (n = 30, age: 11, 8 ± 3, 2). Methods: All samples were analysed using monoclonal antibodies and flow cytometry technique. Results: Peripheral blood T lymphocytes from patients with pauciarticular onset JCA expressed a significantly lower amount of the Bcl-2 protein than T lymphocytes from patients with polyarticular onset JCA (p < 0, 01) and healthy children (p < 0, 05). This differences concerned both CD4 + and CD8 + T cells but CD4 + lymphocytes expressed significantly (p < 0, 05) lower level of Bcl-2 protein in comparison with CD8 + cells in patients with polyarticular onset JCA. There were no correlations between the expression of Bcl-2 and the age of children in all subgroup of patients. There was significant positive correlation (R = 0, 562, p < 0, 05) between the percentage of T lymphocytes with receptor for IL-2 (CD25) and expression of Bcl-2 protein in T cells in children with pauciarticular onset JCA. Conclusion: Our data supported the notion that disturbances in T cell apoptosis may play a role in the immunopathological processes leading to clinical manifestation of JCA, These data suggest also that both polyarticular onset and pauciarticular onset JCA have different pathogenesis and probably distinct aetiologies.